2014
DOI: 10.1371/journal.ppat.1004512
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of Cytomegalovirus IE1 Protein Reveals Targeting of TRIM Family Member PML via Coiled-Coil Interactions

Abstract: PML nuclear bodies (PML-NBs) are enigmatic structures of the cell nucleus that act as key mediators of intrinsic immunity against viral pathogens. PML itself is a member of the E3-ligase TRIM family of proteins that regulates a variety of innate immune signaling pathways. Consequently, viruses have evolved effector proteins to modify PML-NBs; however, little is known concerning structure-function relationships of viral antagonists. The herpesvirus human cytomegalovirus (HCMV) expresses the abundant immediate-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
112
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(120 citation statements)
references
References 87 publications
(117 reference statements)
8
112
0
Order By: Relevance
“…6D). This finding is additionally supported by structural analysis of IE1 CORE , which provides no evidence for the presence of a potential active site with hydrolase activity (30).…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…6D). This finding is additionally supported by structural analysis of IE1 CORE , which provides no evidence for the presence of a potential active site with hydrolase activity (30).…”
Section: Discussionmentioning
confidence: 89%
“…Having shown that lysine 160 is selectively affected by HCMV IE1, the question arose whether IE1 can disturb this As 2 O 3 -mediated degradation of PML. To clarify this issue, we utilized HFF cells with doxycycline-inducible expression of wild-type IE1 or truncated IE1 1-382 (IE1 CORE ), which was described to be sufficient for loss of PML SUMOylation (30,42). As illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations